Robotics technology and flexible automation - Deb, S. R. ([S.l.] : Tata McGraw-Hill Education Private Limited, 1994)
Robotics technology is currently deployed for carrying out multifaceted functions in the areas of fabrication and processing, particularly, in material handling, machine loading, welding, machining, inspection, etc. However, these commercial robots are stiff mechanical units with an elbow, a wrist and usually two fingers without any mobility and with no sense of feeling, hearing, and seeing. The future trends of robotics point towards research on developing intelligent systems like robotic vehicles, space robots, robots for biological and medical application as well as networked robots! The authors, who have over four decades of experience in the industry and academia, have enhanced the coverage of the work by comprehensively adding the latest developments in the field. New topics include robot dynamics, drives, actuator systems, mechatronics, modeling of intelligent systems based on soft computing techniques, CAD/CAM based numerical control part programming, robotic assembly in CIM environment and other industrial applications. Robotics Technology and Flexible Automation will be useful to practising engineers and graduate students interested and engaged in research.